2022
DOI: 10.1111/iju.15102
|View full text |Cite
|
Sign up to set email alerts
|

A national questionnaire survey of Japanese urologists on active surveillance for low‐ and intermediate‐risk prostate cancer

Abstract: AbbreviationsAS = active surveillance DRE = digital rectal examination GS = Gleason score HIFU = high-intensity focused ultrasound IMRT = intensity modulated radiation therapy MRI = magnetic resonance imaging PCa = prostate cancer PS = performance status PSA = prostate-specific antigen

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Conversely, low-risk patients with a Gleason score ≤ 6 may be good candidates for AS. Based on a Japanese national survey, approximately 90% of urologists proposed AS for low-risk disease 32 , and the number of AS cases has increased over the past decades in Japan. However, not all physicians (urologists) recommend AS, even for low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, low-risk patients with a Gleason score ≤ 6 may be good candidates for AS. Based on a Japanese national survey, approximately 90% of urologists proposed AS for low-risk disease 32 , and the number of AS cases has increased over the past decades in Japan. However, not all physicians (urologists) recommend AS, even for low-risk patients.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some patients request treatment even if they have a Gleason score ≤ 6 because they fear disease progression, especially younger patients. Kato et al conducted a national questionnaire survey of Japanese urologists (involving 922 urologists at Japanese Urological Association Teaching Base Hospitals) regarding AS for patients with low-and intermediate-risk prostate cancer 32 and reported that 90.5%, 90%, 39.5%, 48.7%, 15%, and 22% urologists proposed AS for patients in low-risk/no comorbidity, low-risk/with comorbidity, intermediate-risk 3 + 4/no comorbidity, intermediate-risk 3 + 4/with comorbidity, intermediate-risk 4 + 3/no comorbidity, and intermediate-risk 4 + 3/with comorbidity groups, respectively. Therefore, approximately 40% of these urologists proposed AS for intermediate-risk cases.…”
Section: Discussionmentioning
confidence: 99%
“…3 Presently, the authors aimed to clarify the attitude of Japanese urologists toward AS for lowand intermediate-risk PCa by conducting a national questionnaire survey. 4 Despite the clinical evidence supporting AS for low-risk PCa, what prevents AS from being accepted, especially in Japan? This study may provide insights into this question.In this study, approximately 90% of Japanese urologists considered AS an option for the management of low-risk PCa.…”
mentioning
confidence: 99%
“…In this issue of the International Journal of Urology , the authors, using a national questionnaire survey conducted between December 2021 and January 2022, demonstrated that 90% of Japanese urologists proposed AS for low‐risk cases with or without comorbidity 4 . Furthermore, they reported that about 40% of urologists considered AS for favorable intermediate‐risk patients.…”
mentioning
confidence: 99%